Two-Port Circularly Polarized Slot-Coupled Antenna Using Novel AMC Structure - Nathapat Supreeyatitikul; Khwanlada Kakhong; Chuwong Phongcharoenpanich; Jessada Konpang (My University, 2025)
This research introduces a two-port circularly polarized (CP) slot-coupled MIMO antenna with an novel artificial magnetic conductor (AMC) reflector for Vehicle-to-Everything (V2X) technology. The proposed antenna comprises two layers separated by an air gap: the upper layer includes the dual-element slot-integrated MIMO antenna with microstrip-line feeds and defected ground structures (I-shaped slots) for coupling reduction, while the lower layer integrates an 8 × 8 array of AMC units. The AMC enhances gain and improves radiation properties through its reflective behavior. Measured results confirm the antenna’s suitability for V2X applications, achieving a wide return loss bandwidth (RLBW) of 32% (4.72 – 6.61 GHz), axial ratio bandwidth (ARBW) of 21.18% (5.2 – 6.45 GHz), and isolation greater than 19 dB. The antenna attains a peak gain of 8.6 dBic at 5.9 GHz, with an envelope correlation coefficient below 0.003 and diversity gain exceeding 9.98 dB. The key innovation of this work lies in the combination of CP slot-integrated MIMO design with a novel AMC structure to enhance gain and isolation, making it highly effective for V2X wireless networks in modern vehicular communication networks.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Vehicular Ad Hoc Networks (VANETs)